Exploring The Reading Strategies Used By EFL Successful Students - Feny Martina; Susantri, Rama; Melati, Melati; Rakhmanina, Lisa (Edu-Ling: Journal of English Education and Linguistics, 2023)
This research study is intended to determine the strategies of successful students in reading texkbook in Grade XI SMAN 7 Bengkulu city. This research design is qualitative based on case studies. The informant consisted of five students in Class XI SMAN 7 Kota Bengkulu.  Observation and interviews are the instruments of this research used by researchers, then the data is analyzed by triangulation which includes reduction data, display data and drawing conclusions to collect data. The results of this study show that there is one strategy in approaching text, namely previewing. In understanding the text there are four strategies, namely guessing, summarizing, determining the purpose of reading and making conclusions. The strategy in checking comprehension is threefold, rereading. Ask the teacher and also discuss. Each participant used more than one reading strategy. The reading strategy helps them understand the text easily enough so that they can be called good readers  or successful Keywords: EFL Leaners, Reading Strategies, Successful Readers